PENERAPAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 1 KOTA JAMBI - Mailani, Novi; Harjono, Hary Soedarto; Nurfadilah, Nurfadilah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the planning process, implementation, and outcomes of using audiovisual learning media in teaching descriptive text writing in class VII H at SMP Negeri 1 Kota Jambi. The study employs a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research subjects consist of an Indonesian language teacher and randomly selected VII H students. The teacher plans the use of audiovisual media by considering learning objectives, student characteristics, and material suitability. The research findings indicate that the application of audiovisual media has a positive impact, making it easier for students to understand the material, increasing active participation, and improving the quality of students' descriptive text writing. This research finding aligns with previous studies that also found that audiovisual media can enhance students' writing abilities. This media is effective in helping students understand the structure of descriptive texts and express their ideas more clearly and in greater detail. The availability of facilities in schools, such as projectors and audiovisual devices, also plays a crucial role in supporting the successful implementation of this media. Therefore, the use of audiovisual media is expected to continue to be developed in writing education at schools. Keywords: Audio Visual Media, Description Text.